Tiny Talks: A Possibility to Re-signify Teaching and Learning Spaces. A Co-constructed Autoethnography. (2024)
This co-constructed autoethnography study aims to expose the way Tiny Talks create a collaborative sensemaking scenario of our teaching performance as pre-service English teachers from the pedagogic and didactic theories, since we could evidence that there were not spaces where to express situations that could exceed us in our practicum, and a disconnection between the practical knowledge required in the practicum and the theoretical knowledge received in the classes of the Bachelor’s Degree in Foreign Languages in a private university in Medellín. We as participants exposed our beliefs regarding pedagogic and didactic theories in a written narrative; were part of the development of nine Tiny Talks; and we were willing to be observed in our classes twice in the process of data collection just after conducting the Tiny Talks for evidencing the changes in our teaching performance. This process leads us to conclude that Tiny Talks brings us moments such as a relief space, space for knowledge generation, and a collaborative space that allow us not only to express concerns but also to strengthen strategies and beliefs in terms of the educational world.